Negotiating an Illicit Economy in the Time of COVID-19: Selling and Buying Dilemmas in the Lives of People Who Use Drugs in Scotland. (December 2022) - Bancroft, Angus; Parkes, Tessa; Galip, Idil; Matheson, Catriona; Crawshaw, Emma; Craik, Vicki; Dumbrell, Joshua; Schofield, Joe
The impact of COVID-19 itself and societal responses to it have affected people who use drugs and the illicit drug economy. This paper is part of a project investigating the health impacts of COVID-19 related control measures on people who use drugs in Scotland. It examines their roles and decisions as economically situated actors. It does this within a moral economy perspective that places economic decisions and calculations within a context of the network of social obligations and moral decisions. The paper uses a mixed methods approach, reporting on a drug trend survey and in-depth interviews with people who use drugs. It finds they were affected by restrictions in the drug consumption context and changes in the supply context, both in terms of what was supplied and changes in the relationship between sellers and buyers. Face to face selling became more fraught. Participants in more economically precarious circumstances were faced with dilemmas about whether to move into drug selling. The double impact of loss of income and reduced access to support networks were particularly difficult for them. Despite the perception that the pandemic had increased the power of sellers in relation to their customers, many full-time sellers were reported to be keeping their prices stable in order to maintain their relationships with customers, instead extending credit or adulterating their products. The effect of spatial controls on movement during the pandemic also meant that the digital divide became more apparent. People with good access to digital markets and easy drug delivery through apps were in a better position to manage disruption to drug sales contexts. We make recommendations in relation to how policy can respond to the interests of people who use drugs in a pandemic.